Evolution of urban complexes and their influence on population growth and development of the peri-urban spaces in Calimaya, State of Mexico, from 1990 to 2015 - García-González, María Lourdes; Carreño-Meléndez, Fermín; Mejía-Modesto, Alfonso (Papeles de Población, 2017)
This paper aims to show the evolution and influence of housing production in the private sector in expanding urbanization and population growth in Calimaya, State of Mexico, form 1990 to 2015, using qualitative and quantitative techniques, taking basis information from the Secretariat of state and Municipal Urban Development, INEGI and GIS. Statistical, cartographic data, observation and analysis of the process of housing production through urban complexes in Calimaya show on the hand its tendency to spread out of control in the towns of Calimaya Diaz Gonzalez, San Andres Ocotlan and the Concepción Coatipac, on the areas suitable for agriculture that surround forming a disorderly and scattered suburban residential space, and secondly, the rapid population growth and its potential social and environmental impacts of these.